Long-Term Outcome After Pectoralis Major Transfer for Irreparable Anterosuperior Rotator Cuff Tears. (1st February 2017) - Moroder, Philipp; Schulz, Eva; Mitterer, Marian; Plachel, Fabian; Resch, Herbert; Lederer, Stefan
Abstract : Background: Promising short-term outcomes after pectoralis major tendon transfer for the treatment of an irreparable anterosuperior rotator cuff tear have been reported. The purpose of this study was to evaluate the long-term outcome. Methods: Twenty-seven consecutive patients with irreparable anterosuperior rotator cuff tears without advanced cuff arthropathy or advanced humeral head migration were treated with a partial subcoracoid pectoralis major tendon transfer between 2004 and 2005. At an average of 10 years (range, 9 to 11 years) postoperatively, 22 patients (82%) with an average age of 62 years (range, 42 to 74 years) at the time of surgery had a long-term follow-up examination that included the pain score, strength and range-of-motion assessment, Constant score, Simple Shoulder Test (SST), as well as radiographic and ultrasonographic imaging. The long-term results were compared with the preoperative findings as well as the short-term results that were collected from a previous evaluation. Results: The adjusted Constant score increased from 54% to 87% at the short-term follow-up (p < 0.001) and remained improved at the long-term follow-up, with a mean score of 83% (p = 0.001). While the significant improvement of the pain level at the short-term follow-up was maintained at the time of final follow-up (p = 0.001), the increase in strength returned to the preoperative level (p = 0.178), and the improvement in range of motion diminished again over time despite remaining significantly improved (p = 0.029), especially with regard to internal rotation (p < 0.001). At the long-term follow-up, 77% of the patients were very satisfied with the procedure. A third of the patients had no progression of cuff arthropathy, a third had progression by 1 grade, and a third had progression by ≥2 grades. At the time of final follow-up, 1 patient (5%) had undergone revision surgery to reverse shoulder arthroplasty. Conclusions: Pectoralis major tendon transfer for the treatment of irreparable anterosuperior rotator cuff tears results in a significant clinical improvement even 10 years after surgery, especially with respect to pain and internal rotation. Despite long-term radiographic progression of cuff arthropathy, patient satisfaction remains high over time, with a low rate of salvage with reverse shoulder arthroplasty. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.